Determinants of Auditor’s Ethical Sensitivity: Data from South Kalimantan - Widya Ais Sahla; Nurul Mukhlisah; Lea Emilia Farida (Jurnal Dinamika Akuntansi)
This study aims to identify factors that influence the auditor's ethical sensitivity in dealing with work environment situations that will ultimately affect ethical decision making. Specifically this research will examine the influence of ethical reasoning, spiritual well-being, locus of control, age and gender on the auditor's ethical sensitivity. This research is a survey of auditors in South Kalimantan. The analysis technique used is multiple regression. The results showed that spiritual well-being and age did not affect the high and low sensitivity of auditors. While ethical reasoning, locus of control and gender are proven to influence auditor sensitivity.